2007
DOI: 10.1038/ncb1667
|View full text |Cite
|
Sign up to set email alerts
|

Unified mode of centromeric protection by shugoshin in mammalian oocytes and somatic cells

Abstract: Reductional chromosome segregation in germ cells, where sister chromatids are pulled to the same pole, accompanies the protection of cohesin at centromeres from separase cleavage. Here, we show that mammalian shugoshin Sgo2 is expressed in germ cells and is solely responsible for the centromeric localization of PP2A and the protection of cohesin Rec8 in oocytes, proving conservation of the mechanism from yeast to mammals. However, this role of Sgo2 contrasts with its mitotic role in protecting centromeric cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
328
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(347 citation statements)
references
References 47 publications
14
328
1
2
Order By: Relevance
“…Furthermore, recruitment of PP2A that regulates Rec8 cleavage also depends on SgoI in fission and budding yeast (38). Rec8 localization to centromeres in mouse oocytes depends on SgoII and deletion of SgoII leads to fertility defects in mice (23,39). Together with these findings, our data suggest that the Bub1 function affected in our heterozygous model is its role in protecting centromere cohesion through recruitment of shugoshin, PP2A, and Rec8 proteins and prevention of separase-mediated removal of cohesin (19,20).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore, recruitment of PP2A that regulates Rec8 cleavage also depends on SgoI in fission and budding yeast (38). Rec8 localization to centromeres in mouse oocytes depends on SgoII and deletion of SgoII leads to fertility defects in mice (23,39). Together with these findings, our data suggest that the Bub1 function affected in our heterozygous model is its role in protecting centromere cohesion through recruitment of shugoshin, PP2A, and Rec8 proteins and prevention of separase-mediated removal of cohesin (19,20).…”
Section: Discussionsupporting
confidence: 72%
“…Conditional deletion of Bub1 in mice leads to developmental and proliferation defects in mouse embryonic fibroblasts (MEFs) and spermatogonial cells (21) whereas a hypomorphic mouse mutant model that expresses reduced levels of Bub1 shows an increased incidence of tumors (22). In mouse oocytes, Bub1 localizes to kinetochores (10,23), and a dominant-negative form of Bub1 that perturbs the kinetochore localization activity of the wildtype (WT) protein leads to the acceleration of meiosis I, as has also been shown for Mad2 (9,24,25). It was recently shown that specific depletion of Bub1 in mouse oocytes results in chromosome missegregation at meiosis I and loss of cohesion between sister chromatids (26).…”
mentioning
confidence: 99%
“…The role of Sgo in the regulation of mitotic cohesion has been addressed in a number of recent studies, mainly in yeast and human cells McGuinness et al 2005;Vaur et al 2005;Kitajima et al 2006;Tang et al 2006;Kawashima et al 2007;Vanoosthuyse et al 2007;Lee et al 2008). However, this is the first time that the Xenopus egg cell free system, in which vertebrate cohesin was initially characterized, is used.…”
Section: Discussionmentioning
confidence: 99%
“…In Saccharomyces cerevisiae, an organism in which there is no prophase release of cohesin, Sgo1 is not required for cohesion but for sensing tension between sister chromatids (Indjeian et al 2005). Human Sgo2 also acts as a sensor of tension (Huang et al 2007;Lee et al 2008), whereas a number of studies in HeLa cells show that knock down of Sgo1 by small interfering RNA (siRNA) leads to premature separation of the sister chromatids and prometaphase arrest McGuinness et al 2005). Therefore, in these transformed human cells, Sgo1 appears to protect a small population of cohesin both at arms and at centromeres from the prophase pathway (Nakajima et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Such a process could underlie situations in which PP2A activity is responsive to spindle tension. For example, at the second division of meiosis, bipolar pulling forces that arise between the centromere regions of separating chromosomes after anaphase onset are known to cause a centromere-localized molecule (Shugoshin) that binds the B subunit of PP2A to move away from the relevant PP2A substrate, cohesin (8,52,53). It thus has been proposed that these oppositely directed movements eliminate PP2A activity by spatially separating the enzyme from its substrate.…”
Section: Discussionmentioning
confidence: 99%